Hydro-mechanical behaviour of a cement–bentonite mixture along evaporation and water-uptake controlled paths. (March 2023) - Musso, Guido; Vespo, Vincenzo Sergio; Guida, Giulia; Della Vecchia, Gabriele
Abstract: The results of a laboratory investigation on the effects of drying and wetting on the hydro-mechanical behaviour of a cement–bentonite mixture are presented. A large hysteresis along the hydraulic paths was found for what concerns both the water retention and the volume strains. This might be related to the shrinkage of cement bentonite clusters and to the development of micro-cracks, that were observed with a microscope along drying. Macroscopic cracks developed in a squat sample which had been cured for 28 days and was then left to dry in the laboratory environment, while this did not occur in an analogous sample cured for 60 days, possibly in virtue of its higher strength as detected through a pocket penetrometer. Water uptake after partial desaturation of squat and column samples took place in short times with respect to drying, but it did not allow for a full recovery of the initial water content. Electrical Resistivity Tomography (ERT) monitoring provided reliable water content determinations in the high range and correct indication of crack patterns at low water contents. A good reproduction of the experimental results was obtained with a coupled Thermo-Hydraulic model formulated on purpose. Highlights: Effects of drying and wetting on the hydro-mechanical behaviour of cement–bentonite mixture were studied. Large hydraulic hysteresis might be due to the retraction of CB clusters, detected through SEM evidence. ERT provided reliable water content determinations and indication of crack patterns development. Evaporation and water uptake were well reproduced by a thermo-hydraulic numerical model.